A social cognitive perspective of leadership: exploring the impact of a scenario-based leadership training intervention within healthcare settings - Rushton, Emma (2017)
This thesis explores and tests an integrated, social cognitive approach to understanding leadership and developing leaders within healthcare organisations in the United Kingdom. Two studies were implemented; the first involved an assessment of the personal and environmental components of leaders and their followers, as well as the self-reported and follower-rated behaviour of leaders in eight National Health Service (NHS) organisations. The second study involved working with 15 organisations across the NHS to implement and evaluate a scenario-based training intervention which promotes a social cognitive perspective of leadership and draws on the principles of adult learning. The impact of this intervention was examined using a longitudinal design and factors influencing the transfer of leader self-efficacy were explored.